2023
DOI: 10.3389/fimmu.2023.1125912
|View full text |Cite
|
Sign up to set email alerts
|

Unisexual infection with Schistosoma mansoni in mice has the potential to boost the immune response against eggs after challenge infection

Abstract: IntroductionThe complexity of the Schistosoma spp. life cycle and their effective immune evasion strategies, makes vaccine development challenging. Unisexual infection models, that excludes any immunomodulatory effects of the parasite eggs, may contribute to a better understanding of complex immunological processes and identification of new targets for vaccine research. We have recently shown that long-term unisexual infection with schistosomes in mice results in an unpolarized Th1/Th2 response associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A first infection with female cercariae had no effect on the worm burden. Furthermore, we and others have shown that a single-sex infection triggers a non-polarized Th1/Th2 immune response [52,53]. This became particularly clear in transcriptome analyses of spleen tissue from mice infected with male or female or with male and female cercariae 8 weeks after infection.…”
Section: Discussionmentioning
confidence: 65%
“…A first infection with female cercariae had no effect on the worm burden. Furthermore, we and others have shown that a single-sex infection triggers a non-polarized Th1/Th2 immune response [52,53]. This became particularly clear in transcriptome analyses of spleen tissue from mice infected with male or female or with male and female cercariae 8 weeks after infection.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, a transwell system with adult mated male worms in the upper wells confirmed the presence of Sj -miRNAs from MM-derived EVs in HSCs [ 18 ]. Although the function of these Sj -miRNAs in activation of HSCs remains unclear, the results of this study provide evidence that single-sex or bisexual infected male and female schistosome worms have different effects on liver fibrosis [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous S. mansoni infection boosts the host’s immune response against eggs in subsequent infections ( 57 ). Current evidence shows that eggs (and their antigen Smp40) reduce endothelial Cav-1 expression, disrupting endoprotective signaling, leading to dysfunctional phenotype of human and mouse endothelial cells and lung injury ( 58 ).…”
Section: Discussionmentioning
confidence: 99%